The crystal structure of (E)-3-(2-chlorophenyl)-1-ferrocenylprop-2-en-1-one, C19H15ClFeO - Zhang Lilei; Xie Mengru (Zeitschrift für Kristallographie - New Crystal Structures)
C19H15ClFeO, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 10.2693(5) Å, b = 11.2568(6) Å, c = 20.8930(10) Å, α = 80.350(2)°, β = 76.9640(10)°, γ = 86.921(2)°, V = 2319.4(2) Å3, Z = 6, R gt(F) = 0.0534, wR ref(F 2) = 0.0968, T = 170 K.